Innate Sensing of the Gut Microbiota: Modulation of Inflammatory and Autoimmune Diseases - Ignacio, Aline; Morales, Camila Ideli; Câmara, Niels Olsen Saraiva; Almeida, Rafael Ribeiro (Frontiers in Immunology, 2016)
The mammalian gastrointestinal tract harbors a diverse microbial community with which dynamic interactions have been established over millennia of co-evolution. Commensal bacteria and their products are sensed by innate receptors expressed in gut epithelia and in gut-associated immune cells thereby promoting the proper development of mucosal immune system and host homeostasis. Many studies have demonstrated that host-microbiota interactions play a key role during local and systemic immunity. Therefore, this review will focus on how innate sensing of the gut-microbiota and their metabolites through inflammasome and toll-like receptors impact the modulation of a distinct set of inflammatory and autoimmune diseases. We believe that a better understanding of the fine-tuning that governs host-microbiota interactions will further improve common prophylactic and therapeutic applications.